Measuring the fracture energy of bed breakage using a short impact load cell - Dube, Thobile Thenjiwe (Centre for Minerals Research, 2017)
Particle fracture is the elementary process that governs comminution. In industrial machines particle breakage occurs mainly through three mechanisms: impact, abrasion and attrition. Of these mechanisms, impact breakage is known to be the most basic form of particle size reduction. Comminution devices are highly inefficient, as the energy used for particle breakage relative to that consumed by the equipment is low and reported to be between 1-2 %. As such, understanding the fundamentals of particle fracture is crucial for the development of energy efficient particle size reduction methods. Research done towards investigating particle fracture under impact loading has led to the development of several devices which include the twin pendulum device, drop weight tester, Split Hopkinson Pressure Bar, Rotary Breakage Tester and the Short Impact Load Cell. In this study the Short Impact Load Cell (SILC) was used to conduct bed breakage experiments on partially confined particles. Breakage tests using this device were conducted by vertically releasing a steel ball of known mass onto a bed of particles from a known height. The bed rested on a steel rod which was fitted with strain gauges to measure the particle response to impact loading. Tests were conducted on two ores, blue stone and UG2, to investigate the effect of three variables: steel ball mass, drop height and bed depth on the breakage behaviour of particles. The effect of each variable was investigated by evaluating the peak forces obtained, the particle fracture energy and the degree of particle breakage attained. For both ores it was found that the peak force increased linearly with increasing steel ball mass and drop height, and it was found that the drop height had a greater effect on the peak force than the steel ball mass. The maximum peak forces were obtained at one layer of particles and increasing the bed depth generally led to a reduction in the peak force. An exponential relationship was found between the peak force and bed depth, where the peak force decreased with increasing bed depth. It was found that the blue stone particles did not break at the range of input energies used in this work, therefore no fracture energy results were reported for blue stone. The fracture energy values for UG2 were low, where the maximum energy used for particle fracture was 2.7 % of the input energy. There was no direct correlation between the fracture energy and the steel ball mass, drop height and bed depth; however it was found that the bed depth had a larger effect on the fracture energy compared to both the steel ball mass and drop height. The greatest amount of energy used for fracture was generally obtained at the largest input energies using the 357 and 510 g balls. The optimum drop height which resulted in the highest fracture energy was generally found to be either 240 or 300 mm. A bed depth of five layers was found to be the optimum bed depth that allowed for the highest amount of energy to be utilized for breakage. No breakage results were obtained for blue stone due to the hardness and stiffness of the ore. For UG2, tests conducted at the same bed depth showed a trend in which the breakage initially increased greatly with increasing input energy; however at larger input energies the breakage obtained approached a constant value. Although the input energy was varied by changing both the steel ball mass and the drop height, the results showed that the degree of breakage was more dependent on the steel ball mass compared to the drop height. For all tests conducted, the maximum breakage was obtained at one layer of particles and increasing the bed depth led to a decrease in the breakage obtained. The results showed that the fracture energy and the degree of breakage were not directly related. It was found that there is an optimum amount of energy utilized for fracture that leads to the greatest breakage, where an in increase in the energy beyond the optimum point does not significantly affect the breakage obtained.